Knowledge and Severity of Female Urinary Incontinence and Reasons for Not Seeking Treatment - Hadi Susiarno; Ryandra Prakasa; Budi Handono (Faculty of Medicine, Universitas Padjadjaran, 2021)
Urinary incontinence (UI) is a commonly overlooked problem in women, particularly women of post-menopausal age. Despite the medical, social, and hygiene burdens conferred by UI to its sufferers, past studies have shown that only a few among women afflicted with UI sought treatment. This may be due to various reasons: lack of knowledge and awareness of UI or a wrong belief of UI as a natural part of aging. This study aimed to investigate the association between knowledge and severity of UI and reasons for not seeking treatment among post-menopausal women in Bandung, Indonesia. This was an analytic cross-sectional study conducted at the Geriatric and Gynecology Clinic, Dr. Hasan Sadikin General Hospital, in September 2013. Ninety-one women who met the inclusion criteria were interviewed to assess their knowledge of UI. The severity of UI was assessed using Urinary Distress Inventory 6 (UDI-6). Data were analyzed using the chi-square test. Sixty-five respondents (70.7%) had poor knowledge of UI. Knowledge of UI was not associated with awareness of UI as a medical condition (p=0.633). The difference in UI severity was associated with the perception of UI as a normal part of aging (p=0.008). Post-menopausal women are poorly informed regarding urinary incontinence. However, knowledge alone might not be adequate to encourage women to seek treatment. Further studies are needed to investigate women’s reasons for not seeking treatment for UI.